Measuring core body temperature with a non-invasive sensor. (May 2017) - Mazgaoker, Savyon; Ketko, Itay; Yanovich, Ran; Heled, Yuval; Epstein, Yoram
Abstract: In various occupations, workers may be exposed to extreme environmental conditions and physical activities. Under these conditions the ability to follow the workers' body temperature may protect them from overheating that may lead to heat related injuries. The "Dräger" Double Sensor (DS) is a novel device for assessing body-core temperature (Tc ). The purpose of this study was to evaluate the accuracy of the DS in measuring Tc under heat stress. Seventeen male participants performed a three stage protocol: 30 min rest in a thermal comfort environment (20–22 °C, 50% relative humidity), followed by an exposure to a hot environment of 40 °C, 40% relative humidity −30 min at rest and 60 min of exercise (walking on a treadmill at 5 km/h and 2% elevation). Simultaneously temperatures measured by the DS (TDS ) and by rectal temperature (Tre ) (YSI-401 thermistor) were recorded and then compared. During the three stages of the study the average temperature obtained by the DS was within±0.3 °C of rectal measurement. The correlation between TDS and Tre was significantly better during the heat exposures phases than during resting under comfort conditions. These preliminary results are promising for potential use of the DS by workers under field conditions and especially under environmental heat stress or when dressed in protective garments. For this goal, further investigations are required to validate the accuracy of the DS under various levels of heat stress, clothing and working levels. Highlights: In the field, measuring body temperature by the current devices is impractical. The DS derives Tc noninvasively from heat flux gradients. The DS has a potential use in monitoring workers' Tc with acceptable precision.